2009
DOI: 10.1007/s12078-009-9051-7
|View full text |Cite
|
Sign up to set email alerts
|

Odor Memory Performance and Memory Awareness: A Comparison to Word Memory Across Orienting Tasks and Retention Intervals

Abstract: Odor memory has been argued to exhibit unique characteristics in relation to memory for other types of stimuli such as visually presented words. Two experiments investigated episodic recognition performance as well as memory awareness for odors and words across manipulations of orienting task and retention interval. Orienting task mattered little to odor recognition. However, in contradiction with several previous studies, substantial forgetting of odors was found. After controlling for effects of odor identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 51 publications
(69 reference statements)
2
26
0
Order By: Relevance
“…It has been argued that olfactory cognition is set to overestimate stimulation for the purpose of serving as a warning system with safe and liberal decision criteria for detection [ 30 ]. In parallel, liberal decision criteria (i.e., high incidence of false alarms) for short-term recognition of common object odors have also been reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that olfactory cognition is set to overestimate stimulation for the purpose of serving as a warning system with safe and liberal decision criteria for detection [ 30 ]. In parallel, liberal decision criteria (i.e., high incidence of false alarms) for short-term recognition of common object odors have also been reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As noted, studies on odor memory revealed surprisingly little forgetting over time ( Lawless, 1978 ; Murphy et al, 1991 ; Saive et al, 2014 ). This seemed to be valid for longer RIs (days, weeks, and 1 year; Engen and Ross, 1973 ; Lawless and Cain, 1975 ; Olsson et al, 2009 ) as well as for shorter ones (seconds to minutes; Engen et al, 1973 ; Jones et al, 1975 ; Jehl et al, 1994 ). More recent studies have rebutted these results by showing substantial forgetting over time in line with e.g., memory for faces ( Cornell Kärnekull et al, 2015 ).…”
Section: Methodsmentioning
confidence: 79%
“…Indeed, there is evidence that nameable and non-nameable odours may be represented differently in memory (e.g. Zelano, Montag, Khan, & Sobel, 2009), with verbal recoding shown to produce memory effects similar to that shown with words (Olsson, Lundgren, Soares, & Johansson, 2009). To be clear, since verbalisable odours may exhibit PI effects resulting from verbal rather than olfactory perceptions, Experiment 1 employs hard-to-name odours.…”
mentioning
confidence: 99%